PENGARUH ATMOSPHERE DAN RELATIONSHIP MARKETING PADA INDUSTRI KOPI (STUDI KASUS DI COFFEE SHOP KEROBOKAN, BALI) - I Made Chandra Mandira; Ni Luh Gede Resti Purwaningsih (Halu Oleo University, 2024)
Coffee is a commodity that has experienced an increase during the pandemic until now, connoisseurs of all ages have found coffee business opportunities, especially coffee shops in Bali. The purpose of this study is to analyze the effect of atmosphere and relationship marketing on customer loyalty in Coffeeshop in Kerobokan Kelod simultaneously and partially. The method in this study used a quantitative approach by distributing questionnaires to 100 respondents in all coffee shops in Kerobokan Kelod. Checking the validity of the data using the validity test and reliability test. Data analysis techniques in this study used the classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, coefficient of determination test (R2), f-test (f-test), and t-test (t-test). The findings in this study are that atmosphere and relationship marketing have a significant effect on customer loyalty partially and simultaneously.